Molecular markers as predictors of response to perioperative chemotherapy in locally advanced gastric cancer - K. A. Oganyan; A. A. Musaelyan; S. V. Lapin; T. V. Kupenskaya; A. A. Sveсhkova; M. A. Belyaev; A. A. Zakharenko; S. V. Orlov (Успехи молекулярной онкологии)
Introduction. Perioperative FLOT chemotherapy has improved prognosis in patients with locally advanced resectable gastric cancer (GC). However, in 80 % of cases, the tumor is resistant to the therapy, resulting in unnecessary toxicity and delayed surgical treatment.Aim. Evaluation of clinico-morphological patterns of microsatellite instability, HER2 gene amplification, changes in gene copy number and their relationship with the response to perioperative FLOT chemotherapy in patients with locally advanced resectable GC.Materials and methods. The retrospective study included 185 patients. All tumor samples were assessed for HER2 and microsatellite instability status. Among all cases there were 45 patients with locally advanced T2–4N1–2 M0 GC, who underwent a total or subtotal gastrectomy with D2 lymphadenectomy and perioperative chemotherapy with FLOT. Microsatellite instability detection was performed using fragment analysis, HER2 gene amplification testing – fluorescent in situ hybridization. Also 19 patients were tested for copy number changes of the FGFR1, FGFR2, KRAS, MET, EGFR, CCND1, MYC genes using Multiplex ligation-dependent probe amplification. The endpoints were progression-free survival and objective response rate.Results. Microsatellite instability was detected in 4.8 % (9/185) of GC cases. Microsatellite instability was associated with advanced age (p = 0.005), low grade of differentiation (p = 0.011), presence of tumor-infiltrating lymphocytes (p = 0.0004), and high preoperative CA 72–4 levels (p = 0.025). Prevalence of HER2 amplification was 7.5 % (14/185). It was associated with low grade of differentiation (p = 0.048) and metastasis in regional lymph nodes (p = 0.037). PFS in patients with HER2-positive (HER2 – human epidermal growth factor receptor 2) GC treated with perioperative FLOT chemotherapy (4/45) was significantly lower than in patients with HER2-negative GC: the median was 156 and 317 days, respectively (hazard ratio 0.49; 95 % confidence interval 0.16–1.47; p = 0.0006). There was no correlation between the presence of the alteration and ORR (p = 1.0). Progression-free survival in GC patients with KRAS amplification (3/19) was significantly lower comparing with patients without it: the median was 98 and 327 days, respectively (hazard ratio 0.29; 95 % confidence interval 0.07–1.19; p <0.0001). There was no association between an increase in KRAS copy number and objective response rate (p = 1.0). For microsatellite instability and other studied markers no statistically significant correlation with progression-free survival and objective response rate was found (p >0.05).Conclusion. The presence of HER2 and KRAS amplification have been shown as promising predictive markers of the treatment failure in patients treated with perioperative FLOT chemotherapy for locally advanced resectable GC.